Effect Of Winding Angle Due To Internal Pressure In Hybrid Polymer-Metal Cylindrical Composite - Abdul Rahim, Khairul Izman (2014)

(untitled)
The hybrid cylindrical composite structure using glass polymer types and metal alloy as the liner subjected to high internal pressure is still under development stage. Glass-fiber with quasi-isotropic lamination overwrap stainless steel is selected to be the main focus in this research. By modelling the hybrid cylindrical composite structure using finite element method (FEM), the stress and burst pressure are simulated. Based on the design of the hybrid cylindrical composite structure, sample of hybrid cylindrical composite structure are fabricated. Finally, through an experiment known as the split disk test, a series of tests were conducted. These tests were carried out to obtain the actual stress value of the structure and to observe the sequence of failure that occurred. Based on the simulation and experimental result, the polymer composite component failed first before the stainless steel, which leads to the catastrophic failure